A systematic review of the pharmacological modulation of autobiographical memory specificity - Cawley, Emma; Piazza, Giulia; Das, Ravi K.; Kamboj, Sunjeev K. (Frontiers in Psychology, 2022)
Background: Over-general autobiographical memory (AM) retrieval is proposed to have a causal role in the maintenance of psychological disorders like depression and PTSD. As such, the identification of drugs that modulate AM specificity may open up new avenues of research on pharmacological modelling and treatment of psychological disorders. Aim: The current review summarizes randomized, placebo-controlled studies of acute pharmacological modulation of AM specificity. Method: A systematic search was conducted of studies that examined the acute effects of pharmacological interventions on AM specificity in human volunteers (healthy and clinical participants) measured using the Autobiographical Memory Test. Results: Seventeen studies were identified (986 total participants), of which 16 were judged to have low risk of bias. The presence and direction of effects varied across drugs and diagnostic status of participants (clinical versus healthy volunteers). The most commonly studied drug – hydrocortisone – produced an overall impairment in AM specificity in healthy volunteers (g=-0.28, CI [-0.53, 0.03], p=0.03), although improvements were reported in two studies of clinical participants. In general, studies of monoamine modulators reported no effect on specificity. Conclusion: Pharmacological enhancement of AM specificity is inconsistent, although monaminergic modulators show little promise in this regard. Drugs that reduce AM specificity in healthy volunteers may be useful experimental-pharmacological tools that mimic an important transdiagnostic impairment in psychological disorders.